The Quick Growth of the Catholic Church in Manggarai: A Phenomenology of Conversion and Some Explanations - Borgias M., Fransiskus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2015)
Since the arrival of Christianity together with the colonial rulers, Manggarai, Flores, Indonesia, undergoes physical and spiritual changes. These changes can be explained with theory of intellectual voluntarism (the free will of the repentant) and theory of structural determinism (enforcement by external factor). It appears that the changes in Manggarai happen because of the mixture of both factors in their diverse variants, such as the political-economical, educational, social-services related, and religious-theological factors. There are two horizons in the whole process of encounter and transformation in this area. On the one hand, there is the horizon of European Christian missionaries (supported by government), and on the other hand, the horizon of the Manggarain, with their cultural life in the broadest sense of the word. The two horizons fuse to each other in one drama of cultural encounter throughout the growth of the Church. Following the hermeneutical discourse of Gadamer, it might be said that the fusion of the two horizons results in the emergence of a new face of unique local and contextual Christianity. In its uniqueness and locality, it has also something to be contributed to the universal Church.